Behavioral parent training for ADHD children: a mixed methods study - Hari Wahyu Nugroho; Mei Neni Sitaresmi; Indria Laksmi Gamayanti (Indonesian Pediatric Society, 2017)
Background Management of ADHD requires multimodal treatments. Parental participation is one of the most important factors for effective ADHD treatment.Objective To investigate the effectiveness of behavioral parent training combined with routine clinical care, in reducing ADHD symptoms in children.Methods Quantitative and qualitative methods were combined in this study. This study was conducted at 3 growth and developmental clinics in Central of Java, on June-July 2016. The quantitative aspect was assessed by comparing ADHD quotient scores at pre- and post-intervention, while the qualitative aspect by intensive parental interviews. Parents of children with ADHD were randomized with block random sampling. In the treatment group, parents received behavioral training for 7 weeks, along with weekly routine clinical care for their children. The control group received only routine clinical care of the children. Six parents in the treatment group were randomly selected for intensive interviews.Results A total of 67 parents with their children were involved. Both groups’ ADHD quotient scores improved post-intervention. The treatment group ADHD quotient score was reduced from 120.53 to 116.41 (effect size Cohen’s d 0.68). The control group ADHD quotient score was reduced from 121.74 to 119.83 (effect size Cohen’s d 0.23). Mean difference post-intervention in both group was not significant (p=.161). After behavioral parent training, communication between parents and children increased and parents’ capability in directing their children’s daily activity increased.Conclusion Behavioral parent training can not enhacing effectiveness of routine clinical care to reduce ADHD symptoms in children.